IMPLEMENTASI KEBIJAKAN KEMENTERIAN AGAMA TERHADAP PENYELENGGARAAN TAMAN PENDIDIKAN AL-QUR’AN DI KABUPATEN PASURUAN - Usman Usman (Adabiyah : Jurnal Pendidikan Islam, 2015)
The purpose of this study was to determine the policy of the Religious Affairs toward the organizing of Al-Quran Education School in Pasuruan, as well as the implementation and results. It used qualitative research through descriptive. The technical data collection used were interviewing, observation, and documentation. The data analysis used was an interactive model of Miles and Huberman with three (3) steps: data reduction, data presentation, and conclusion. Checking the data validity was done by verifying data with 4 (four) criteria: internal validity, external validity, reliability, and objectivity. The result was the standardization of the Ministry of Religion Policy for Al-Quran Education School in Pasuruan implemented through programs or activities of certification and accreditation. the results of implementation were the typology TPQ. Tose were 4% of modern /pilot project TPQ, 33% of standard TPQ, 48% of developing standard TPQ, and 15% of traditional recitation TPQ